1988
DOI: 10.2527/jas1988.66123033x
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Reproductive Performance in Crude Protein-Restricted Beef Cows: Return to Estrus and Conception

Abstract: A study was conducted to evaluate the effect of a deficiency in dietary crude protein intake on postpartum reproductive performance of first-calf beef cows. Forty primigravid Hereford heifers were randomly assigned to two groups that were fed isocaloric (100% NRC requirements) diets containing .96 (adequate) or .32 (deficient) kg crude protein per head daily. Animals were individually fed from 150 d prepartum to 40 d postpartum and then were group-fed until the end of the experiment at 110 d postpartum. Total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 13 publications
0
30
0
6
Order By: Relevance
“…Em alguns casos, foram observadas (1998-1999) e 3 (1999-2000) nos tratamentos MMC (mistura mineral completa o ano todo), MM (mistura mineral completa nas águas e mistura mineral sem fosfato bicálcico na seca) e MMR (mistura mineral completa nas águas e mistura mineral sem fosfato bicálcico + concentrado) na seca Means tendências à resposta reprodutiva em vacas suplementadas com fósforo (S'Thiago et al, 2000), mas é possível que em alguns desses trabalhos um número insuficiente de fêmeas tenha sido utilizado para permitir discriminação estatística do efeito de tratamentos (Wu & Satter, 2000). Alguns trabalhos (Fordyce et al, 1997, Sasser et al, 1988 têm mostrado melhoras na taxa de concepção e redução no período de serviço de animais suplementados com energia e proteína durante o pré-parto, provavelmente por melhora da CC dos animais ao parto, embora o mecanismo pelo qual a suplementação melhora a fertilidade não seja totalmente conhecido. Jolly et al (1994) indica que o estresse nutricional atua diretamente e/ou indiretamente no eixo hipotálamo-hipófise-ovários, suprimindo o reinício da atividade ovariana pós-parto e afetando a fertilidade.…”
Section: Resultsunclassified
“…Em alguns casos, foram observadas (1998-1999) e 3 (1999-2000) nos tratamentos MMC (mistura mineral completa o ano todo), MM (mistura mineral completa nas águas e mistura mineral sem fosfato bicálcico na seca) e MMR (mistura mineral completa nas águas e mistura mineral sem fosfato bicálcico + concentrado) na seca Means tendências à resposta reprodutiva em vacas suplementadas com fósforo (S'Thiago et al, 2000), mas é possível que em alguns desses trabalhos um número insuficiente de fêmeas tenha sido utilizado para permitir discriminação estatística do efeito de tratamentos (Wu & Satter, 2000). Alguns trabalhos (Fordyce et al, 1997, Sasser et al, 1988 têm mostrado melhoras na taxa de concepção e redução no período de serviço de animais suplementados com energia e proteína durante o pré-parto, provavelmente por melhora da CC dos animais ao parto, embora o mecanismo pelo qual a suplementação melhora a fertilidade não seja totalmente conhecido. Jolly et al (1994) indica que o estresse nutricional atua diretamente e/ou indiretamente no eixo hipotálamo-hipófise-ovários, suprimindo o reinício da atividade ovariana pós-parto e afetando a fertilidade.…”
Section: Resultsunclassified
“…72:843-851 (Dec. 1992) 1970; Short and Adams 1988). Protein (Witt et al 1958;Sasser et al 1988) and energy (Dziuk and Bellows 1983;Houghton et al 1985; Rode et al 1986) (Wiltbank et al 1964;Dunn et al 1969), there is still some controversy about the level of postpartum nutrition that ensures early rebreeding and maximum pregnancy rates (Lamond 1970;Rutter and Randel 1984 The cows were weighed and scored for BC (Lowman et al 1916) for the grain-fed cows ( Table 2). …”
mentioning
confidence: 99%
“…Prepartum nutrition has been reported to impact (Sasser et al 1988;Selk et al 1988;Marston et al 1995;Shoup et al 2015) or not affect (Corah et al 1974;Stalker et al 2006;Winterholler et al 2012) postpartum reproductive performance in beef cows. Marston et al (1995) reported that when cows were supplemented with increased energy amounts (7.0 vs 3.6 Mcal ME/d), cows had increased pregnancy rates.…”
Section: Methodsmentioning
confidence: 99%
“…Embryo transfer became a viable option for the North American beef industry during the early 1970s (Hasler 2003). Considerable evidence exists which implicates that prepartum nutritional management will improve subsequent reproductive performance in beef cattle (Sasser et al 1988;Selk et al 1988;Lents et al 2008). Prepartum nutrition affects BW and BCS (Stalker et al 2006;Bohnert et al 2013) and can alter circulating hormone concentrations (Wiley et al 1991;Lalman et al 1997) that are important in cattle achieving reproductive success.…”
Section: Introductionmentioning
confidence: 99%